PERANAN KUALITAS PELAYANAN TERHADAP KINERJA RUMAH SAKIT ( STUDI PADA RAWAT INAP RUMAH SAKIT ISLAM WAFA KEPANJEN KAB. MALANG) - Churiyah, Madziatul (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2007)
Service quality has an important role in enhancing company performance. A key factor to win the competition lied in the company ability to make its costumer satisfy. Service quality has already become main focus for RSI Aisyiah, and the service quality enhancement is the most serious challenge that must be done in all sectors. In a tight competition and fast business environment changes, consistency in quality service is necessary to maintain superiority in competition, so the RSI WAFA Kepanjen performance could be enhanced. The objective of this research is to analyze influence the service quality, which consists of reliability, responsiveness, empathy, assurance, and tangible, on hospital performance. The number of sample is 78 from 350 respondents (Annual Data Report RSI Aisyiah, 2007), by purposive sampling technique. The respondent criteria are patients who had been hospitalized in RSI WAFA Kepanjen. Data were analyzed by multiple regression models.Result of research descriptively shows score mean obtained that reliability, responsiveness, empathy, assurance, and tangible dimensions have been well applied in RSI WAFA Kepanjen and in its marketing, which is indicated by costumer retention of RSI WAFA , is relatively high. The multiple regression analysis shows that the service quality has significant impact on marketing performance simultaneously in RSI WAFA Kepanjen and partially, all five dimensions of service quality have significant impact on marketing performance of RSI WAFA. It means that hospital performance can be obtained by maintaining service quality improvement. The improvement of hospital performance and patient satisfaction can be effectively done if all existing elements have a high commitment and loyalty to the company in maintaining service quality. Due to that reason, RSI WAFA Kepanjen need to apply proactive and partnership marketing in an effort to approach the costumer and by enhancing service quality could also give contribution on hospital performance